The Impact Of The Construction Of A Steam Power Plant (PLTU) In The Socio-Economic Life Of The Community In Lampoko Village, Balusu District, Barru Regency - Muliati, Muliati; Rosdiana, Rosdiana (SEAN Institute, 2024)
This study aims to determine the impact of coal-fired power plants in the socio-economic life of the community in Lampoko Village, Balusu District, Barru Regency. The type of research used is qualitative, the type of data used is qualitative data, data sources are primary data and secondary data, data collection techniques by means of observation, interviews and documentation, data analysis techniques through data collection stages, data reduction, data presentation and conclusion drawn/verification. The results of this study show that the construction of coal-fired power plants in the social life of the community in Lampoko Village, Balusu District, Barru Regency has less positive impact, seen from the aspects of public health, labor absorption, and job expansion. And the construction of coal-fired power plants in the economic life of the community in Lampoko Village, Balusu District, Barru Regency has less positive impact, seen from the increase in community income, economic development, and the development of the economic structure.